Analisis Faktor-Faktor Yang Mempengaruhi Rating Sukuk - Melis, Kalia (Jurnal Ilmiah Mahasiswa FEB, 2016)
his research aimed to analyze the influence of liquidity ratio (current ratio), profitability ratio (return on assets), leverage ratio (debt to equity ratio) and auditor reputation toward sukuk rating. The sample used are sukuk that listed in Indonesian Stock Exchange and also rated by PT PEFINDO during 2009-2013. Based on purposive sampling method, sample amount of 65 samples. The analysis in this research used multiple analysis linier regression.The result shown that liquidity (current ratio), profitability (return on assets), leverage (debt to equity ratio) and auditor reputation simultaneously take effect to sukuk rating. Liquidity partially take effect to sukuk rating. Meanwhile, profitability, leverage and auditor reputation does not influence rating sukuk.Keywords: sukuk rating, current ratio, return on assets, debt to equity ratio, auditor reputation, multiple linier regression